2012
DOI: 10.5897/ajar11.2500
|View full text |Cite
|
Sign up to set email alerts
|

The effect of planting distance on yield of beans (Vicia faba L.) under drip irrigation system

Abstract: . Differences on the number of branches plant -1 and weight of pods were not significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
2
7
1
Order By: Relevance
“…Result obtained from Table 3 showed that there were no significant differences within the mean of cultivation distances (cm) on plant's diffusion. This result contradicts with the results in research [4] in which the distances of agriculture had a significant effect on the diffusion of plants, because the researchers used agricultural distances greater than the distances we used in our research (20. 30, 40 cm).…”
Section: Plant's Diffusion (Cm)contrasting
confidence: 99%
See 2 more Smart Citations
“…Result obtained from Table 3 showed that there were no significant differences within the mean of cultivation distances (cm) on plant's diffusion. This result contradicts with the results in research [4] in which the distances of agriculture had a significant effect on the diffusion of plants, because the researchers used agricultural distances greater than the distances we used in our research (20. 30, 40 cm).…”
Section: Plant's Diffusion (Cm)contrasting
confidence: 99%
“…The results indicated in Table 2 showed that, the higher distance between plants, the lower in plant height (inverse relationship). Cultivation of plants on a distance of 20 cm achieved a significant increase (81.32 cm) in plant height, followed by a decrease in plant height when cultivating at a distance of 25 cm (74.98) and this distance achieved a significant decrease from the distance of 30 cm (65.91 cm), this is due to decreasing the spaces, plants are more competitive with sunlight and such competition decreases as the increases of distance [4], these results obtained from cultivated broad bean under drip irrigation in that research, also our results were coincide with the findings of [21], but the researcher was conducted his research under rainy conditions . The mean concentration of 3.0 ml (H A ) organic fertilizer / liter water, achieved the highest mean length of the plant (82.07 cm) followed by the concentration of 1.5 ml /liter water (75.29 cm).…”
Section: Plant Height (Cm)mentioning
confidence: 97%
See 1 more Smart Citation
“…The highest seeds yield of faba bean resulted from the cultivars Misr 3 and Giza 843 (tolerant/resistant cultivars) which gave increases in seed yield (ardab/fed) by 158.2 and 95.9% in 2014/15 season and by 129.5 and 111.9% in 2015/16 season compared to susceptible cultivar Giza3. These results were in agreement with those obtained by Gadalla et al (2010), Amer et al (2012), Ismail (2013) and Ibrahim et al (2014).…”
Section: On Faba Bean Yield and Yield Componentssupporting
confidence: 94%
“…Gadalla et al (2010) proved that Giza3 was susceptible cultivar and Giza843 was tolerant to Orobanche infection, which had the lowest Orobanche tubercles/plant. Amer et al (2012) found that the differences between varieties were affect significant on growth, plant height, number branches plant -1 , pod length and number of seed pod -1 , respectively. Ismail (2013) revealed that faba bean variety Misr1 decreased number and dry weight of Orobanche spikes by 17.3 and 17.0%, respectively, as compared with variety Giza 40.…”
Section: Introductionmentioning
confidence: 96%